Efektivitas Metode Penilaian 360 Derajat dalam Meningkatkan Disiplin Guru di MTsN 3 Labuhan Batu - Farihin Abdillah Fattah; Neliwati; Hirwansyah; Rizza Fikri Al-Faris (As-Syar i: Jurnal Bimbingan & Konseling Keluarga, 2025)
This research aims to evaluate the effectiveness of the 360 ​​degree assessment method in improving teacher discipline at MTsN 3 Labuhan Batu. The research method used is qualitative, with data collection techniques in the form of interviews, observation and documentation. The research results show that the 360 ​​degree feedback method is effective in improving teacher discipline, especially in indicators of attendance, punctuality and compliance with rules. However, the application of this method faces challenges such as work culture resistance that avoids criticism and limited understanding of techniques for providing constructive feedback. These findings provide important implications for the development of performance evaluation strategies in educational institutions, especially in creating a transparent and collaborative work culture.